Ventajas terapeúticas del uso de la asociación de ampicilina con Uncaria Tomentosa (Uña de Gato) en pacientes con procesos infecciosos - Lahoud S., Víctor (2001)
The scientific demostrated the therapeutic advantages of administraing 500mg. ampicilim, associated with 45 mg. freeze-dried extract of Uncaria Tomentosa. In comparison with the administration of ampicilim 500 mg. associated with the anti-inflammatory piroxican, in acute infectius processes of the oral cavity. 40 patients diagnosed with acute infectious processes in the oral cavity, were divided in two groups. Twenty patients of the experimental group were administered a capsule containing 500mg. ampicilim with 45 mg. of Uncaria tomentosa, every 8 hours during 5 days, for oral via; the treatment proved to be effective in 90% of the clinical cases and failures were of 10%, there were not been report adverse effects of gastrointestinal nature in 100% of the treated cases. The control group was constituted by 20 patients who were administered for oral via, a capsule of 500 mg. ampicilim, and a capsule of the anti-inflammatory piroxican, every o hours during 5 dys, the treatment was effective in 70% of the clinical cases and failures were of 30%. It was eport adverse affects of gastrointestinal nature in 27% of the treated clinical cases.